The Effectiveness of Interactive Approach Reading Skill - Firda Alisya Maslahat (Journal of English Language and Education, 2023)
Reading is a cognitive process influenced by the reader's brain, emotions, and beliefs, wherein they interpret the written words. The interactive approach is an instructional technique that holds promise for enhancing students' reading skills. This approach is considered effective because it promotes collaborative work, structured procedures, and encourages active participation and responsibility through different roles and tasks. The research results indicate that the post-test scores of both the experimental and control groups were statistically significant at a level of ≤ 0.05. The mean score of the post tests in the experimental group showed a greater increase compared to the control group. Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. The post test scores reveal that the experimental group achieved a mean score of 88.57, while the control group attained a mean score of 81.56. This suggests that the experimental group outperformed the control group in terms of reading skills. Consequently, there is a significant difference in reading skills between students taught using the interactive approach and those taught using student worksheets.